2020
DOI: 10.1016/j.apsusc.2019.144235
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a porous silver doped TiO2 coating on titanium substrates synthesized by plasma electrolytic oxidation

Abstract: The objective of this study was the development of Ag-rich antibacterial coatings on titanium (Ti) to prevent post-operative infections. A series of Ag-doped TiO2 coatings were synthesized on Ti discs by plasma electrolytic oxidation (PEO) in an electrolyte containing Ag nanoparticles (AgNPs). The incorporation, distribution and chemical composition of the AgNPs on Ti were determined using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS). The crystalline structure and wettability of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 66 publications
1
50
0
Order By: Relevance
“…In the TiN film, the Ra was equals to 13.2 nm and WCA was equal to 28.3°, but with the silver incorporation (8.6 at.%), the roughness and WCA changed to 15.1 nm and 16.6°respectively. Other study case was performed by Thukkaram et al [55] which fabricated Ag-doped TiO 2 in order to obtain antibacterial properties. They revealed that with the silver incorporation into the films, Ra and WCA has shown opponent behaviour.…”
Section: Roughness and Wettabilitymentioning
confidence: 99%
“…In the TiN film, the Ra was equals to 13.2 nm and WCA was equal to 28.3°, but with the silver incorporation (8.6 at.%), the roughness and WCA changed to 15.1 nm and 16.6°respectively. Other study case was performed by Thukkaram et al [55] which fabricated Ag-doped TiO 2 in order to obtain antibacterial properties. They revealed that with the silver incorporation into the films, Ra and WCA has shown opponent behaviour.…”
Section: Roughness and Wettabilitymentioning
confidence: 99%
“…Bacterial infections may appear in postoperative wounds if the procedure for the sterilization of the instruments and implants was not strictly followed [ 3 ]. Bacteria are capable of forming a biofilm structure, thus protecting themselves against the environment and the human immune system [ 4 , 5 ]. At the implant site, an infection develops, which spreads to the whole body and may cause life-threatening complications [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photons with sufficient energy can create an electron–hole pair, and, as a result, the excited electron in the conduction band reduces oxygen to superoxide, while the hole in the valence band oxidizes water molecules to hydroxyl ions [ 30 ]. Moreover, titania has high durability as well as chemical activity and stability under ultraviolet (UV) light [ 31 , 32 ], which, in addition to its water splitting ability, makes it useful for antimicrobial treatment, water purification, self-cleaning purposes [ 33 , 34 , 35 , 36 ], and material passivation [ 37 ]. The species formed through redox reactions at the surface are sufficiently powerful to decompose organic molecules or microbes, leading to the self-cleaning ability of TiO 2 .…”
Section: Importance Of Tiomentioning
confidence: 99%